Failure of prosthetic screws on 971 implants - Carolina Schäffer Morsch; Caroline Freitas Rafael; Juan Felipe Montero Dumes; Gabriella Mercedez Peñarrieta Juanito; João Gustavo Oliveira de Souza; Marco Aurélio Bianchini (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the presence of failures in prosthetic screws and whether these failures are related to the type of prosthesis, abutment angulation and presence or not of intermediate. Methods: Two-hundred and sixty-seven patients were evaluated at the Federal University of Santa Catarina, totaling 971 external hexagonal implants in place for at least one year. A Tobit regression model for censored variables was used and the explanatory variables were subjected to percentage analysis. Results: The results demonstrated a relationship between the failure in prosthetic screws and the investigated factors with a significance of F=0.003 and p<0.05. The percentage analysis showed that the prosthetic screw failed in 8.82% of 238 unitary prostheses and 10.1% of 773 multiple prostheses. Among 912 abutments, 9.43% failed and in the 59 angled abutments, failures appeared in 15.25%. A total of 200 prostheses were placed over the implant platform and 13% failed. A total of 771 prostheses were made over abutment and 8.95% of these screws failed. Conclusions: Through multiple linear regression it could be concluded that the type of prosthesis showed no significant influence on the prosthetic screw failure, but other variables were related to this mechanical failure. There was a significant relationship among the variables, demonstrating the need for greater attention in choosing the type of prosthesis, the abutment angulation and whether the prosthesis will be placed directly on the implant platform or on the abutment.